Multidisciplinary Rehabilitation for People with Parkinson's Disease: A Systematic Review and Meta-Analysis. (28th February 2022) - Seid, Abubeker Alebachew; Demirdel, Ertugrul; Aychiluhm, Setognal Birara; Mohammed, Ahmed Adem
Abstract : Introduction . Guidelines endorse to implement an integrated and multidisciplinary team approach in the management of people with Parkinson's disease (PD). However, there is no net and clear finding that shows the supremacy of multidisciplinary team interventions over conventional interventions for people with PD. Therefore, we perform a systematic review and meta-analysis to determine the supremacy of multidisciplinary interventions for people with PD. Methods . A systematic review and meta-analysis of randomized controlled trials were conducted. PubMed, Physiotherapy Evidence Database, Cochrane Library, and Google Scholar were searched from inception until May 2021. Randomized controlled trials comparing multidisciplinary intervention with conventional physiotherapy were included. The outcome measures were gait balance, disability status, quality of life, and depression level. The PEDro scale was used to systematically appraise methodological quality. Two reviewers screened, extracted, and performed a quality assessment of included studies independently. Review Manager V.5.4 (Cochrane Collaboration) software was used for statistical analysis. Heterogeneity was analyzed using I 2 statistics, and a standardized mean difference with 95% CI and P value was used to calculate the treatment effect for outcome variables. Results . A total of 6 studies with 1260 participants were included. The average PEDro methodological quality score was 6.67. No statistically significant difference between multidisciplinary and conventional rehabilitation on functional capacity (SMD: 0.69; 95% CI: −0.13, 1.51; P = 0.10 ), disability status (SMD: 0.65; 95% CI: −0.16, 1.46; P = 0.11 ), and quality of life (SMD: 0.28; 95% CI: −0.31, 0.59; P = 0.08 ) was found. However, there is a statistically significant improvement in caregivers' anxiety levels in the multidisciplinary group (SMD: 0.39; 95% CI 0.06, 1.73; P = 0.02 ). Conclusion . This systematic review and meta-analysis show no significant difference between multidisciplinary and conventional rehabilitation on functionality, disability, and quality of life. Caregivers' anxiety levels show improvement following multidisciplinary interventions. However, large-scale studies with long-term follow-up were required for concrete and clinical recommendations.